2017
DOI: 10.1021/acs.jpcc.7b00516
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanosegregation on the Phase Behavior of Fluorinated Ionic Liquids

Abstract: Fluorinated ionic liquids (FILs) have received increasing attention due to their physicochemical properties. They allow us to enlarge the tuneability power of traditional ionic liquids. With the aim to understand the thermodynamic behavior of these compounds, a study of solid−fluid transitions using differential scanning calorimetry, thermogravimetric analysis, rheology, and molecular dynamics simulation has been performed. A comparison between different cations, anions, and hydrogenated alkyl chains was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 58 publications
5
48
0
Order By: Relevance
“…The present set of SANS data provides then the first direct experimental evidence of the existence of structural heterogeneities related to the spatial segregation of fluorinated tails in FRTILs, in agreement with the proposal by Ferreira et al 51 . Such clusters originate from the assembly of fluorous tails embedded into the polar three dimensional matrix that is formed by the charged moieties that interact through strong Coulombic interactions, in a way that is very similar to the spatial segregation of alkyl tails in more common RTILs.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The present set of SANS data provides then the first direct experimental evidence of the existence of structural heterogeneities related to the spatial segregation of fluorinated tails in FRTILs, in agreement with the proposal by Ferreira et al 51 . Such clusters originate from the assembly of fluorous tails embedded into the polar three dimensional matrix that is formed by the charged moieties that interact through strong Coulombic interactions, in a way that is very similar to the spatial segregation of alkyl tails in more common RTILs.…”
supporting
confidence: 92%
“…[31][32][33][34] ). More recently different investigations focused on ILs containing fluorinated anions 22,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . Among these studies some focused on symmetric bis(perfluoroalkanesulfonyl)amide (C n F 2n+1 SO 2 ) 2 N anions (hereinafter indicated as [IM xx ], where x corresponds to the perfluoro alkyl chain length), paired with the diethylmethyl(2-methoxyethyl)ammonium (hereinafter indicated as [DEME]) cation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they commonly show low surface tension and/or are chemically and biologically inert . Therefore, they are potential candidates to substitute fluorinated organic compounds in different applications, for example, as surfactants, gas absorbents, lubricants and refrigerants . It has also been shown that fluorinated ILs can be used as gas carriers, electrolytes in fuel and solar cells, and in lithium batteries, in catalysis and in many more applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first structural study by Shen and coworkers [17] focused on a fluorinated protic ionic liquid, a subsequent Molecular Dynamics investigation from the Margulis group appeared [18], where the concept of triphilic ionic liquids that we proposed in our first study [13] has been atomistically described. More recently a series of Molecular Dynamics studies by Canongia Lopes and coworkers appeared [29][30][31][32], proposing, on the basis of computational work, a scenario where alkyl domains and fluorous ones tend to segregate from the charged three-dimensional network. Although not focusing on fluorinated anions that lead to the formation of fluorous domains, several studies have been dedicated to the exploration of structural properties in pyrrolidinium-based ILs, merging diffraction and computational techniques [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%